Painting of ‘Dadaji ka Pagaliya’ - Temples of India Project Team (Jio Institute, 2024)
The painting of ‘Dadaji ka pagaliya’ depicts a semi-upon chhatri, which is usually built as a memorial of the deceased. It is painted on the ceiling of the mandapa (pillared hall) of the Bhandasar Temple. There is a chhatri (memorial) painted in white, likely to resemble the marble construction. A water body surrounds it. On the open pedestal of the chhatri, there are two footprints. Dadaji in this painting could be a reference to one of the four Dada Gurus of the Jain tradition, namely, Jinadatta Suri (1075-1154 CE), Jinachandra Suri Manidhari (1140-1166 CE), Jinakushala Suri (1280-1332 CE) and Jinachandra Suri II (1541-1613 CE). Their memorials are often found next to Jain temples.